Pengaruh Permaianan Bakboy terhadap Pembelajaran Keterampilan Passing Bola Basket pada Siswa Kelas XI SMA Negeri 1 Grabagan - Muhammad Irfan; Hasan Saifuddin; Rohmad Apriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of bakboy games on the basketball passing skills of 11th grade students at Grabagan 1 Public High School. Based on the results of field observations, the research problem stems from the low level of students' skills in accurate passing. This study used a pre-experiment with a One Group Pretest-Posttest Design. The research sample consisted of 36 students selected using purposive sampling. The research instrument was a ball throwing and catching (passing) test. The treatment was carried out over 6 meetings through the application of the bakboy game, which trains hand-eye coordination, arm muscle power, and movement coordination. The results of the analysis showed an increase in the average score for each passing skill from 48.33 for chest passes, 48.61 for bounce passes, and 48.47 for overhead passes in the pretest to 59.72 for chest passes, 59.72 for bounce passes, and 59.58 for overhead passes in the posttest. The normality test showed that the data was normally distributed, while the t-test (Paired Sample T-Test) results obtained chest pass, bounce pass, and overhead pass Sig. (2-tailed) < 0.05 values, which means there was a significant difference between the pretest and posttest results. The findings indicate that the bakboy game is effective in improving ball passing skills. Conclusion, physical education teachers are encouraged to utilize traditional games as an alternative learning strategy that is engaging, contextual, and incorporates local cultural values. Keywords: Traditional Games, Bakboy, Physical Education Learning, Basketball Passing